REMOVAL OF OIL FROM PRODUCED WATER USING SUGARCANE BAGASSE: EQUILIBRIUM AND KINETIC STUDIES - Kachako, Ahmad Isah; Muhammad, Idris Misau; Makwashi, Nura; Abdulkarim, Abdulwadud Y. (FUDMA JOURNAL OF SCIENCES, 2024)
The improper disposal of produced water poses a significant environmental challenge, necessitating effective treatment measures to mitigate its harmful impact. This study explores the potential of sugarcane bagasse (SB) as a biosorbent, both in its original form and modified state for removal of oil from produced water. The SB samples were collected, washed, dried, and characterized for functional groups, surface morphology, and elemental composition using FT-IR, SEM and EDS equipment respectively. The analysis identified various elements in both modified and unmodified SB. The impact of biosorbent dose, contact time, pH, and temperature on oil removal from produced water was investigated. The results showed a rapid increase in oil uptake by modified SB with increase in dosage, reaching a maximum of 97.80%. Unmodified SB exhibited a gradual increase in oil uptake, leveling off at 81.32%. Modified SB demonstrated a shorter contact time compared to unmodified one. Isotherm studies revealed that the Langmuir isotherm best fit the data for both modified and unmodified SB, with R2 value of 1 and 0.997, respectively. On the other hand, the equilibrium parameter RL were found to be 0.00001 and 0.0194 for modified and unmodified SB as biosorbent respectively. Biosorption kinetics were tested using pseudo-first order and pseudo-second-order kinetic models. The results indicated that the biosorption process followed the pseudo-second-order model, with R2 values of 0.998 and 0.999 for modified and unmodified SB, respectively. In conclusion, both modified and unmodified sugarcane bagasse demonstrate promising potential as effective materials for oil removal from produced water.